2021
DOI: 10.3389/fpsyg.2021.675532
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Social Responsibility Development in a Volleyball Hybrid Positive Youth Development Program: A Mixed Methods Approach

Abstract: Positive Youth Development (PYD) programs are being used to foster holistic growth in children and adolescents. The hybridized application of two or more programs of this type has acquired special relevance in recent years. Although their application is common in the school context, there are few research studies that attempt their implementation in an extracurricular context. This study analyzed the effects of an intervention based on a hybrid PYD program on personal responsibility (PR) and social responsibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
0
7
0
3
Order By: Relevance
“…In this work, guidelines and parameters from the literature have been followed, taking into account previously made research and interventions in order to design the present proposal [19,[22][23][24][25]34,59]. Furthermore, an expert with more than five years of expertise in TPSR reviewed the framework of the proposal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, guidelines and parameters from the literature have been followed, taking into account previously made research and interventions in order to design the present proposal [19,[22][23][24][25]34,59]. Furthermore, an expert with more than five years of expertise in TPSR reviewed the framework of the proposal.…”
Section: Discussionmentioning
confidence: 99%
“…For the development of the aforementioned values, various interventions have been carried out in the literature with the objective of promoting them separately [18][19][20][21][22][23]. However, the work of Hellison [24] and his teaching personal and social responsibility model (TPSR) must be highlighted, which, through physical activity and sport, aims to bring about significant changes in the values of the participants.…”
Section: Respect Equality and Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous studies have proved the feasibility of TPSR and SE hybridization by observing that the two models share the same learning theory [ 23 ], while SE and CL offer a situated learning context with meaningful activities [ 24 ]. Practical investigations have shown that TPSR and SE may be successfully combined as long as the implemented project intends to provide students with the opportunity to experience all five levels of responsibility in the framework season of SE [ 25 , 26 , 27 ]. In other words, hybridizations conducted among pedagogical models refer to extracting and merging the key features of two models or using one model as a foundation and adding other significant elements from the other.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of a larger research project, whose aim was to design a hybridized TPSR+SE program [ 51 ] and apply it to competitive youth volleyball players in order to assess its effects on peer leadership, personal and social responsibility [ 52 ], decision-making and atmosphere, as well as to analyze its implementation fidelity and the perception of the participants (i.e., players and coach) about the structure of the intervention.…”
Section: Introductionmentioning
confidence: 99%